Broadband near-infrared emission of La3Ga5GeO14:Tb3+, Cr3+ phosphors: energy transfer, persistent luminescence and application in NIR light-emitting diodes. Issue 34 (3rd August 2020) - Bai, Biao; Dang, Peipei; Zhu, Zhongli; Lian, Hongzhou; Lin, Jun
Abstract : A broadband near-infrared La3 Ga5 GeO14 :Tb 3+, Cr 3+ phosphor with high efficiency was achieved via design of energy transfer for NIR LEDs. Abstract : A La3 Ga5 GeO14 :Tb 3+, Cr 3+ near-infrared phosphor with high efficiency was prepared by a high-temperature solid-state method. The synthesized samples were analyzed by X-ray diffraction (XRD), diffuse reflectance spectroscopy, photoluminescence spectroscopy (PL&PLE), fluorescence decay curves and temperature dependent photoluminescence spectroscopy. Due to the highly efficient energy transfer from Tb 3+ to Cr 3+ ions, at an excitation wavelength of 373 nm, all La3 Ga5 GeO14 :Tb 3+, Cr 3+ samples show strong emission bands in the range of 400–1300 nm, and the optimal doping concentration is under the conditions of x = 2.5 mol% and y = 1.4 mol%. In addition, the La2.975 Ga4.986 GeO14 :0.025Tb 3+, 0.014Cr 3+ phosphor showed excellent thermal stability, and the emission intensity at 423 K maintained 62% of the original value at 298 K. NIR pc-LED devices were prepared by combining a La2.975 Ga4.986 GeO14 :0.025Tb 3+, 0.014Cr 3+ phosphor with a 460 nm blue light emitting chip. Photoluminescence with a total output power of 3.018 mW could be achieved at a driving current of 160 mA, indicating the potential application in night vision lighting.